Does Managers Opportunistic Motive Moderate the Relationship Between CSR Disclosure and Firms Market Value of Equity? Study on the Listed Banking Companies in the Dhaka Stock Exchange - Rahman, Mashiur; Rasid, Siti Zaleha Abdul (Journal of Asian Business Strategy, 2021)
Despite the growing prevalence of CSR disclosure, it is unclear what fundamental importance the market places on it. Previous literature has also shown attention to whether those organizations with more outstanding CSR disclosure scores are more Market Value of Equity (MVE) by market respondents. Empirical confirmation, nonetheless, delivers inconclusive outcomes concerning the path of these associations. This study aims to convey onward the standing research accomplishments and fill the research gaps that encompass examining the possible relationship between CSRD and MVE and the moderating effect of discretionary loan loss provisions (DLLP) to observe the right direction in this inconclusive relationship. Also, through a generalized valuation framework stimulated by Ohlson, this research examines whether CSRD is value relevant and, especially, the moderating effect of DLLP on this association. This study is based on a sample of 30 firm-year observations using cross-sectional data methodology for an example of Bangladeshi listed banking companies (both conventional and Islamic perspective) of the Dhaka Stock Exchange (DSE) over the year 2019. Regarding DLLP, this study investigates earnings aggressiveness through loan loss provisions. More importantly, this study measure CSR disclosure by developing a CSR Disclosure index based on prior studies on CSR and global reporting initiatives (GRI) guidelines. This study’s expected finding anticipated that CSR reports could positively affect the stock price, and DLLP may negatively affect this association’s direction. Our results could have several ramifications for financial institutions, investors, and policymakers.